MgO/Fe₂O₃ ratio mineralization-responsive intervals and their constraints on Cr-Ni-Co mineralization: From regional geochemical mapping to large-scale anomaly focusing and targeting - Zhao An; Zhenhua Zheng; Tao Wang; Qingyun Wang; Li He; Changwei Qi; Mingfu Zhao; Yulong Li; Youning Wei; Dong Zhang; Xiaojun Dong; Yong Wang (Journal of Geochemical Exploration, 2026)

Migration and enrichment mechanisms of selenium, zinc, and iodine in the soil–plant–animal continuum of Yushu, Qinghai–Tibet plateau: insights from environmental geochemical factors - Zhao An; Siqi Han; Tao Wang; Haikui Tong; Li He; Changwei Qi; Qinyu Liu; Sheng Xue; Youning Wei; Yulong Li; Xiaojun Dong (Environmental Monitoring and Assessment, 2026)

Enrichment and sources of major and trace elements in the Qinghai-Tibetan Plateau: a case study of the Golog Prefecture - Zhen Yao; Haixu Zhang; Hao Zhang; Youning Wei; Yao Niu (Environmental Monitoring and Assessment, 2024)

Investigating the environmental capacity of soil heavy metals and its determinants in agro-pastoral regions of the qinghai-tibetan plateau - Siqi Han; Lu Dai; Qingyu Liu; Youning Wei; Yao Niu; Kaili Xu (Environmental Geochemistry and Health, 2024)

Experimental and numerical study on suppressing coal dust deflagration flame with NaHCO3 and MPP - Yansong Zhang; Youning Zhang; Jing Shi; Mengting Cao; Xiangrui Wei; Lei Shi; Xiang Wang (Fuel, 2024)

Transcriptomic Signatures of Pearl Oyster Pinctada Maxima in Response to Acute Salinity Stress - Haijun Wei; Mingqiang Chen; Zhenghua Deng; Jing Sun; Jingru Yang; Wang Zhao; Youning Li; Zhenhua Ma; Yu Wang; Gang Yu (Frontiers in Marine Science, 2022)
Acute salinity stress can impact many physiological processes of marine shellfish. The responses of Pinctada maxima to salinity stress, especially the osmotic pressure regulation and immune response, are of great significance to health. To investigate the molecular changes in response to acute salinity stress, the pearl oysters were transferred from 30 ppt (C) to 40 ppt (HS) and 20 ppt (LS) for 12 h, and the transcriptome analysis was conducted on the gills. Compared to the control, there were 6613 (3253 up-regulated and 3360 down-regulated) differentially expressed genes (DEGs), 4395 (2180 up-regulated and 2215 down-regulated) DEGs observed in HS and LS, respectively. The related molecular biological processes and potential functions were explored from enrichment analysis. A total of 332 KEGG pathways (including 1514 genes) and 308 KEGG pathways (including 731 genes) were enriched in C vs. HS and C vs. LS, respectively. In addition, there are 1559 DEGs shared by C vs. HS group and C vs. LS group, and the results of the KEGG function annotation showed that 7 DEGs were involved in membrane transport, and 34 DEGs were involved in the immune system. The correlation network for expression of genes shows that the expression of 3 genes was significantly correlated with each other in membrane transport, and there were significant correlations between the expression of 27 genes in immune response. The results of this study will be of great value in understanding the molecular basis of salinity stress adaptation in the pearl oyster P. maxima .

Heavy metal contamination of urban topsoils in a typical region of Loess Plateau, China - Youning Hu; Dexiang Wang; Lijing Wei; Bin Song (Journal of Soils and Sediments, 2014)